AB2 Y-shaped miktoarm star conductive polyaniline-modified poly(ethylene glycol) and its electrospun nanofiber blend with poly(ε-caprolactone). Issue 46 (23rd May 2015) - Massoumi, Bakhshali; Davtalab, Somayeh; Jaymand, Mehdi; Entezami, Ali Akbar
<x xml:space="preserve">Abstract</x> The aim of this study is the synthesis, and characterization of novel type AB2 Y-shaped miktoarm star conductive polyaniline-modified poly(ethylene glycol), and preparation of its electrospun nanofibers blend with poly(ε-caprolactone).